The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3847/1538-4357/836/1/55
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Heating Mechanisms in a Supra-arcade Plasma Sheet Formed after a Coronal Mass Ejection

Abstract: We perform a detailed analysis of the thermal structure of the region above the post-eruption arcade for a flare that occurred on 2011 October 22. During this event, a sheet of hot plasma is visible above the flare loops in the 131Å bandpass of the Atmospheric Imaging Assembly (AIA) on the Solar Dynamics Observatory (SDO). Supra-arcade downflows (SADs) are observed traveling sunward through the post-eruption plasma sheet. We calculate differential emission measures using the AIA data and derive an emission mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 41 publications
(58 reference statements)
7
55
0
Order By: Relevance
“…12 and 32. In the event of 2011 October 22, observed from the face-on perspective, Reeves et al (2017) found temperature peaking in an elongated ridge lying just above the arcade. They observed SADs occurring above it and even passing through it.…”
Section: Downflows In the Plasma Sheetmentioning
confidence: 93%
See 2 more Smart Citations
“…12 and 32. In the event of 2011 October 22, observed from the face-on perspective, Reeves et al (2017) found temperature peaking in an elongated ridge lying just above the arcade. They observed SADs occurring above it and even passing through it.…”
Section: Downflows In the Plasma Sheetmentioning
confidence: 93%
“…When an eruption is viewed face-on, its trailing plasma sheet appears as a tall, broad, fan-like structure above the post-flare arcade (Švestka et al 1998), offering complimentary insight. Of particular note are elongated dark structures, called supraarcade downflows (SADs), observed to move sunward through the plasma sheet (McKenzie & Hudson 1999;Innes et al 2003;Sheeley et al 2004;Khan et al 2007;McKenzie & Savage 2009;Savage & McKenzie 2011;Guo et al 2013;Reeves et al 2017). Supra-arcade fans viewed edge-on sometimes exhibit downward-moving loops, called supra-arcade downflowing loops (SADLs) interpreted as SADs viewed from a different perspective (Savage & McKenzie 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures persist for long times in the late phase of an eruption (e.g. Hanneman & Reeves 2014;Savage et al 2012), lasting much longer arXiv:1910.05386v1 [astro-ph.SR] 11 Oct 2019 than the conductive cooling time (Reeves et al 2017). This finding indicates that there must either be some heating mechanism in the vicinity of the current sheet that keeps the plasma from cooling, or a suppression of the thermal conduction in this region (or both).…”
Section: Introductionmentioning
confidence: 99%
“…Recent high temporal and spatial resolution measurements make the detailed analysis of erupting solar coronal plasma possible. Most coronal analyses assume ionization equilibrium to determine the physical properties of the erupting plasma (Cheng et al 2012;Hannah & Kontar 2013;Patsourakos et al 2013;Tripathi et al 2013;Hanneman & Reeves 2014;Lee et al 2015Lee et al , 2017Reeves et al 2017). In ionization equilibrium, the responses of the Atmospheric Imaging Assembly (AIA) on board Solar Dynamic Observatory and X-ray Telescope (XRT) on board Hinode are functions of temperature alone.…”
Section: Introductionmentioning
confidence: 99%